PENGARUH LINGKUNGAN KERJA FISIK DAN KESELAMATAN, KESEHATAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SUKSES TUNGGAL MANDIRI BAGIAN PRODUKSI DI TANGERANG - Muhamad Maulana Hakim; Hamdi Supriadi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to determine the influence of the Physical Work Environment and Occupational Safety and Health on Employee Performance at PT. Sukses Tunggal Mandiri, Production Division in Tangerang, both partially and simultaneously. This research applies a quantitative approach with an associative method. The sampling technique used is saturated sampling, namely all employees of the production division of PT. Sukses Tunggal Mandiri, totaling 80 respondents. Data collection was carried out through questionnaires. Data analysis employed validity and reliability tests, multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The results show that the Physical Work Environment has a positive and significant effect on employee performance, with a calculated t-value greater than the t-table (9.264 > 1.991) and a significance value less than 0.05 (0.01 < 0.05). Occupational Safety and Health also have a positive and significant effect on employee performance, with a calculated t-value greater than the t-table (14.527 > 1.991) and a significance value less than 0.05 (0.01 < 0.05). Simultaneously, the Physical Work Environment and Occupational Safety and Health have a significant effect on employee performance, with a calculated F-value greater than the F-table (104.355 > 3.115) and a significance value less than 0.05 (0.01 < 0.05). The coefficient of determination (R²) of 0.730 indicates that both variables contribute 73.0% to the dependent variable, while the remaining 27.0% is influenced by other variables outside this study.